2000
DOI: 10.1111/1540-6229.00805
|View full text |Cite
|
Sign up to set email alerts
|

The Pricing of Seasoned Equity Offerings: Evidence from REITs

Abstract: Real estate investment trusts (REITs) have been a very active sector in the capital market over the last few years. This paper examines the pricing of seasoned equity offers by equity REITs during 1991–1996. Consistent with Parsons and Raviv's model, we find that SEOs by REITs are underpriced with respect to both the closing price on the day before and the closing price on the day of the offer. Underpricing depends on the institutional ownership of the firm's common stock. Issues by firms with higher instituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
3
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(69 citation statements)
references
References 13 publications
4
55
3
3
Order By: Relevance
“…Other different studies such as: Ghosh et al (2000); Hadlock and James (2002); Frank and Goyal (2003), Berger and Bonaccorsi (2006), found a positive relationship between capital structure and firm's performance…”
Section: The Static Trade-off Theorymentioning
confidence: 84%
See 2 more Smart Citations
“…Other different studies such as: Ghosh et al (2000); Hadlock and James (2002); Frank and Goyal (2003), Berger and Bonaccorsi (2006), found a positive relationship between capital structure and firm's performance…”
Section: The Static Trade-off Theorymentioning
confidence: 84%
“…Roden and Lewellen (1995) used a sample of 48 U.S. firms for the period [1981][1982][1983][1984][1985][1986][1987][1988][1989][1990] and found a positive relation between profitability and capital structure. In their researches Ghosh et al (2000) and Hadlock and James (2002) concluded that highly profitable firms use high-level of debts. Margaritis and Psillaki (2010) He found a positive and significant relation between financial leverage and firm's performance.…”
Section: The Static Trade-off Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…A number of prior studies provide empirical evidence supporting a positive relationship International Finance and Banking ISSN 2374-20892016 between capital structure and corporate financial performances like Nirajini & Priya (2013), Abu Rub (2012), San & Hang (2011), Margaritis & Psillaki (2010), Frank & Goyal (2003), Holz (2002), Hadlock & James (2002), Ghosh et al (2000), Champion (1999), Roden & Lewellen (1995), Petersen & Rajan (1994), Givoly et al (1992); Malanic et al (2013). As for this positive relationship, these studies concludes that profitable firms (either firms with higher financial performance) will tend to have a large portion of debt finance in their capital structure, there are several reasons behind this situation.…”
Section: A Significant Positive Relationship Between Capital Structurmentioning
confidence: 99%
“…However, the results documented were contradictory and mixed. Some studies have reported that positive relationships (Ghosh et al 2000) also support the argument. Several others have reported a negative relationship between debt and financial achievement like Fama and French (1998) and Simerly and Li (2000).…”
Section: Review Of Literaturementioning
confidence: 74%